Discrimination in clinical settings and its relationship to depression and anger in women living with HIV - Moral de la Rubia, José; Segovia Chávez, María Petra (UANL. Facultad de Medicina, 2014)
Objectives: To describe the frequency of feared discrimination in various social situations and of perceived discrimination in clinical settings, as well as to study the relationship between discrimination and depression and anger in women living with human immunodeiciency virus (HIV). Material and methods: The scale of Feared and Perceived Discrimination for Women with HIV (DTP-40-MV), the Beck Depression Inventory (BDI-2), and the Anger Expression scale of State-Trait-anger expression inventory (STaXi-2-aX/eX) were applied to a random sample of 200 women living with HIV. Results: These women feared being discriminated against, perceived discrimination upon the review of medical records, but perceived little discrimination in clinical care. a model with good adjustment to the data showed that the fear of being discriminated against creates a disposition toward perception of discrimination in the clinical settings (latent variable with 2 indicators: review of the medical records and clinical care) and increases cognitive/affective depressive symptoms; higher anger control decreases the anger manifestation; greater discrimination perceived in the clinical settings decreases anger control, which facilitates the expression of anger and slows cognitive/affective depressive symptoms; and these latter symptoms sensitize the perception of discrimination before the clinical records. Conclusion: Feared discrimination is a clinically relevant aspect due to its frequency and effect on depressive symptoms and perception of discrimination before the review of medical records.